The Influence of Service, Innovation, Integrity on Taxpayer Compliance with Education as a Moderating Variable at the UPT PPD/Samsat Karimun Office - Rezy Trilestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: This study examines the effects of service, innovation, and integrity on taxpayer compliance, with education as a moderating variable at the UPT PPD/Samsat Karimun office. Methodology/approach: A quantitative descriptive method was applied with 156 respondents. Data were analyzed using Partial Least Squares (PLS-SEM) via SmartPLS 4.0. Results/findings: Service and integrity significantly influence taxpayer compliance, while innovation does not. Innovation significantly affects education, which in turn impacts compliance. Education mediates the effect of service on compliance, but not for innovation or integrity. Conclusions: Service quality and integrity play critical roles in boosting compliance, particularly when supported by effective education. Innovation enhances education, but not compliance directly. Limitations: The study is limited to one region and taxpayer segment, potentially restricting generalizability. Contribution: This research offers insights for improving tax compliance through service enhancement and educational innovation, especially in regional administrative settings.